Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13018-020-02041-6
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA LEF1-AS1 attenuates apoptosis and inflammatory injury of microglia cells following spinal cord injury

Abstract: Background Spinal cord injury (SCI) is associated with health burden both at personal and societal levels. Recent assessments on the role of lncRNAs in SCI regulation have matured. Therefore, to comprehensively explore the function of lncRNA LEF1-AS1 in SCI, there is an urgent need to understand its occurrence and development. Methods Using in vitro experiments, we used lipopolysaccharide (LPS) to treat and establish the SCI model primarily on micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…In this review, the lncRNA/circRNA-miRNA-mRNA regulatory network also exists in microglia and astrocyte mediated neurological diseases, including SCI (Figure 1; Shao et al, 2020; FIGURE 1 | The lncRNA/circRNA-miRNA-mRNA regulatory network in microglia and astrocyte regulated neurological diseases. Xu S. et al, 2020;Zhao Q. et al, 2020;Cui et al, 2021;Xiang et al, 2021;Chen et al, 2022), TBI (He et al, 2021;Liu N. et al, 2021;Meng et al, 2021), cerebral IRI (Figure 1; Wang et al, 2020c;Yang et al, 2021), stroke (Figure 1; Qi et al, 2017;Han B. et al, 2018;Tian et al, 2021;Zhang M. et al, 2021), epilepsy (Figure 1; Feng et al, 2020;Han C. L. et al, 2020;Wan and Yang, 2020;Xiaoying et al, 2020), neuropathic pain (Figure 1; Chen M. et al, 2020), PD (Figure 1; Cao et al, 2018Cao et al, , 2021, and depression (Figure 1; . We also found that some therapies can impair the ncRNA-glial cell axis and thus inhibit disease development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, the lncRNA/circRNA-miRNA-mRNA regulatory network also exists in microglia and astrocyte mediated neurological diseases, including SCI (Figure 1; Shao et al, 2020; FIGURE 1 | The lncRNA/circRNA-miRNA-mRNA regulatory network in microglia and astrocyte regulated neurological diseases. Xu S. et al, 2020;Zhao Q. et al, 2020;Cui et al, 2021;Xiang et al, 2021;Chen et al, 2022), TBI (He et al, 2021;Liu N. et al, 2021;Meng et al, 2021), cerebral IRI (Figure 1; Wang et al, 2020c;Yang et al, 2021), stroke (Figure 1; Qi et al, 2017;Han B. et al, 2018;Tian et al, 2021;Zhang M. et al, 2021), epilepsy (Figure 1; Feng et al, 2020;Han C. L. et al, 2020;Wan and Yang, 2020;Xiaoying et al, 2020), neuropathic pain (Figure 1; Chen M. et al, 2020), PD (Figure 1; Cao et al, 2018Cao et al, , 2021, and depression (Figure 1; . We also found that some therapies can impair the ncRNA-glial cell axis and thus inhibit disease development.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-222-5p can target RAMP3 3 UTR and inhibit RAMP3 expression. Enhanced RAMP3 expression or miR-222-5p inhibitor can promote cell apoptosis and increase TNF-α and IL-6 expressions in LPS-treated microglia (Cui et al, 2021). LncRNA lymphoid enhancer-binding factor 1 (LEF1) antisense RNA 1 (LEF1-AS1) is up-regulated in LPStreated microglia cells that are collected from the central nervous system of normal rats.…”
Section: Spinal Cord Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…The M1 phenotype elicits pro-inflammatory activity with the release of pro-inflammatory factors such as IL-6 and TNF-α, while the M2 phenotype is characteristic of anti-inflammatory activity induced by the release of several anti-inflammatory factors such as IL-10 and TGF-β ( 27 , 28 ). LPS induces activation of M1 microglia ( 28 ), facilitates the apoptosis of microglia, and decreases the cell survival rate ( 29 ). Our results demonstrated that overexpression of miR-124-3p could alleviate the damage of LPS to microglia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, reductions in SNHG5 decreases the viability of these cells 12. Furthermore, inhibiting the upregulation of the lncRNA LEF1-AS1 after SCI decreases microglial apoptosis and the inflammatory response 13. Recently, we performed a study indicating that many mRNAs are involved in the alleviation of SCI using HBO 14.…”
mentioning
confidence: 99%